2013
DOI: 10.1111/1574-6941.12138
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins with a broader antimicrobial spectrum prevail in enterococcal symbionts isolated from the hoopoe's uropygial gland

Abstract: The use of compounds produced by symbiotic bacteria against pathogens in animals is one of the most exciting discoveries in ecological immunology. The study of those antibiotic metabolites will enable an understanding of the defensive strategies against pathogenic infections. Here, we explore the role of bacteriocins explaining the antimicrobial properties of symbiotic bacteria isolated from the uropygial gland of the hoopoe (Upupa epops). The antagonistic activity of 187 strains was assayed against eight indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 41 publications
5
46
0
Order By: Relevance
“…In accordance with a possible process of symbiont selection and the effect of environments determining their bacterial community, we found that E. faecalis, the species with the greatest antibiotic activity (35), is the culturable bacterium that is prevalent in hoopoe glands (36). Thus, it is possible that the community of symbionts in the UG of hoopoes is a plastic trait conditioned by particularities of the nest environment each year.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In accordance with a possible process of symbiont selection and the effect of environments determining their bacterial community, we found that E. faecalis, the species with the greatest antibiotic activity (35), is the culturable bacterium that is prevalent in hoopoe glands (36). Thus, it is possible that the community of symbionts in the UG of hoopoes is a plastic trait conditioned by particularities of the nest environment each year.…”
Section: Discussionsupporting
confidence: 68%
“…Although we cannot rule out the possible presence of bacteria that cannot be cultured, our results imply a certain specialization in hosting enterococci. Earlier studies have shown the relationship of bacteriocin production to the antimicrobial capacity of isolated colonies and also the association between genotypes and antimicrobial properties (15,35,36). Moreover, we know that hoopoes derive fitness advantages from harboring these symbionts (14,21), suggesting a mutualistic relationship between enterococci and hoopoes.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Antimicrobial peptides (AMPs) are one of the types of antimicrobial agents used to treat infection diseases (6). Natural antibacterial peptides have a wide antimicrobial spectrum (7), particularly with the ability to eradicate multidrug-resistant bacteria (8), and antibacterial peptides exhibit good thermal stability and solubility in water. One of the best-studied AMP is human LL-37, which is the only cathelicidin peptide found in humans.…”
Section: Introductionmentioning
confidence: 99%